Phytochemical studies on the aerial parts of Sarcococca hookeriana (Baillon) of Nepalese origin - Rai, Narayan P.; Lama, Bimala; Subedi, Shiva P.; Taylor, W. C.; Manandhar, M. D. (Journal of Nepal Chemical Society, 2006)
Two known pregnane type of alkaloids, axillaridine A and spiropachysine, and an unidentified pregane alkaloid along with oleanolic acid and stigmasteryl glucoside have been isolated from chloroform extract of the aerial parts of Sarcococca hookeriana. The structures of the alkaloids are established on the basis of spectral analysis of 1H-NMR, 13C-NMR, HMQC, COSY and HMBC spectrum. All compounds were isolated for the first time from S. hookeriana. So far, species of Sarcococca was not reported to contain spiropachysine which was initially reported as a novel alkaloid from Pachysandra terminalis SIEB. et ZUCC.(Buxaceae). DOI: 10.3126/jncs.v21i0.215 Journal of Nepal Chemical Society Vol.21 2006 pp.8-15